ANALYSIS OF VITAMIN D LEVELS & COMPLETENESS OF COVID-19 VACCINE WITH RECURRENT COVID-19 INFECTIONS: Hubungan Kadar Vitamin D dan Kelengkapan Vaksin COVID-19 dengan Kejadian Infeksi COVID-19 Berulang pada Dosen Universitas Malahayati - Nurjanah, Siti; Hermawan, Dessy; Aryastuti, Nurul; Muhani, Nova; Furqoni, Prima Dian; Sary, Lolita; Widodo, Slamet (Amerta Nutrition, 2024)
Background: There is a continued increase in the fatality rate of COVID-19 pandemic despite the apparent containment of the virus. In September 2022, the death toll from this disease has exceeded 150 thousand individuals. Furthermore, Vitamin D has been observed for its correlation with the immune system. Objectives: This study aimed to analyze correlation between blood vitamin D levels, completeness of COVID-19 vaccine, and compliance with health protocols for recurrent infection. Methods: This analytical observational study with a cross-sectional method examined correlation between blood vitamin D levels, vaccine completeness status, as well as compliance with health protocols, age, and gender. The population consisted of 62 lecturers at Malahayati University, Bandar Lampung, who were willing to volunteer as subjects. The method used was non-probability sampling and the inclusion criteria were individuals infected with COVID-19 in 2022, resulting in 47 samples. The collected data was analyzed using the chi-square test and logistic regression test. Results: The results showed that there was a significant correlation between the completeness status of COVID-19 vaccine (p-value=0.001) with an OR of 8.24 and 8.47, as well as low levels of vitamin D in the blood (p-value=0.007) and recurrent infection. Conclusions: The possibility of recurrent COVID-19 infection was increased when there were lower levels of vitamin D in the bloodstream and a less comprehensive response to vaccine.